USING OPEN GOVERNMENT DATA FOR ECONOMIC DEVELOPMENT - Petrović, Nevena; Milić, Petar; Prlinčević, Bojan (The European Journal of Applied Economics, 2022)
Publishing of open government data brings enormous benefits both to the provider and consumers. From one side, government increases its transparency and enables development of smarter and richer solution, while from the other side enables variety of stakeholders to extract new information and create value from them. In this paper we investigate applicability of open government data for economic development and creation of value from published data. We explore different aspects of open government data consumption, such as effectiveness, transparency and quality and how they interrelate. They are of extremely importance for valorisation of open government data, and we will show that leveraging economic value of OGD must be accompanied by government ability to enable the availability of high quality of OGD.
Keywords: e-government; open data; transparency; quality; economic development